Sistem Pengambilan Keputusan Untuk Menentukan Tingkat Kecanduan Game Online Menggunakan Metode Weighted Product - Muh. Hadal Ali Sam; Muhammad Miftah Farid; Dewi Fatmawati Surianto (Sakura Publisher, 2025)
Playing online games is one of the activities that many people do to entertain themselves in the midst of their busy daily lives. The existence of several genres in online games certainly makes the game more exciting and entertaining. However, excessive and unlimited use as a means of entertainment can have a negative impact, such as online game addiction. In addition, not everyone realizes that they have developed this type of addictive behavior towards the game. As a result, a person who experiences online game addiction tends to be less interested in other activities, feels restless when not playing online games, decreased academic achievement, social relationships and health. For this reason, the utilization of a decision-making system with the weighted product method is very necessary to determine the level of online game addiction. Therefore, the purpose of this research is to develop a decision-making system to determine the level of online game addiction using the weighted product (WP) method. This research consists of several assessment criteria, namely playing time, frequency of play, level of satisfaction playing games, financial expenses, social interactions and physical problems. in this study, manual calculations were carried out with excel and also used a system to determine the level of online game addiction from several alternatives.